Helping Hispanic Family Caregivers of Persons With Dementia "Get the Picture" About Health Status Through Tailored Infographics. (11th June 2019) - Arcia, Adriana; Suero-Tejeda, Niurka; Spiegel-Gotsch, Nicole; Luchsinger, Jose A; Mittelman, Mary; Bakken, Suzanne
Abstract: Background and Objectives: Caregivers need to understand their health status and the disabilities of the care recipient to engage in effective health management. Infographics tailored with personal health data are a promising approach to facilitating comprehension, particularly for individuals with low health literacy/limited English proficiency. Such approaches may be especially important for dementia caregivers given the high care burden. Research Design and Methods: Guided by the Health Belief Model and the Data-Frame Theory of Sensemaking, we conducted iterative participatory design sessions with Hispanic family caregivers ( N = 16) of persons with dementia. We created multiple prototype infographic designs to display scores on validated instruments of topics such as caregiving burden, overall health, and psychological distress. We retained and refined designs participants judged to be easily comprehensible. Analysis focused on identifying the graphical elements that contributed to the comprehensibility of designs and on evaluating participants' reactions to the designs. Results: Successful infographics used intuitive scaling consistent with caregivers' perspective of dementia as inevitable decline. Participants reacted to infographics by describing the self-management actions they would take to address the health issue at hand. Discussion and Implications: Tailored infographics supported caregivers' comprehension of their health status and served as cues to engaging in self-management. As such, they should be presented in the context of informational support that can facilitate selection of appropriate next steps. This can mitigate the potential mental and physical health consequences of caregiving and enable caregivers to continue to care for their relatives with dementia with less damage to their own well-being.